Three knights of faith on Job’s suffering and its defeat - Verbin, Nehama (International journal of philosophy and theology, 2017)
The paper explores the manners in which suffering, both natural and moral suffering, is understood and defeated in the lives of different ‘knights of faith,’ who emerge in ‘conversation’ with the book of Job. I begin with Maimonides’ Job who emerges as a ‘knight of wisdom’; it is through wisdom that his suffering is defeated, dissolving into mere pain. I proceed with Kierkegaard’s Job, who emerges as a ‘knight of loving trust,’ who defeats suffering by seeing it as a divine gift, and by obediently and lovingly accepting it as such. Through his loving trust, suffering transforms into blessedness and joy, without diminishing or disappearing, a transformation referred to as a ‘miracle’ by Kierkegaard. I end with my own Hasidic-inspired Job, whom I portray as a ‘knight of protest,’ who defeats what he takes to be divine abuse by protesting against it, forgiving God while refusing to be reconciled with Him. I argue that it is by paying attention to these diverse Jobs that the complex nature of faith can be elucidated. Moreover, I argue that all three Jobs, despite their differences, may be embraced, both from a philosophically descriptive perspective as well as from a religiously committed one.